2004
DOI: 10.1002/bit.20312
|View full text |Cite
|
Sign up to set email alerts
|

Murine leukemia virus clearance by flocculation and microfiltration

Abstract: Clearance of murine leukemia virus from CHO cell suspensions by flocculation and microfiltration was investigated. Murine leukemia virus is a retrovirus that is recommended by the U.S. Food and Drug Administration for validating clearance of retrovirus-like particles. Due to biosafety considerations, an amphotropic murine leukemia virus vector (A-MLV) that is incapable of self-replication was used. Further, A-MLV is incapable of infecting CHO cells, thus ensuring that infection of the CHO cells in the feed did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Similar wall shear rates were used by Wickramasinghe et al (2004b) for tangential flow microfiltration of minute virus of mice. Higher wall shear rates have also been reported (Akeprathumchai et al, 2004). Since human influenza virus is known to be fragile and easily destroyed, the actual wall shear rate used in a manufacturing process should be sufficiently low to maximize isolation of intact virus particles and minimize damage to virus particles by shear forces during cross flow.…”
Section: Discussionmentioning
confidence: 97%
“…Similar wall shear rates were used by Wickramasinghe et al (2004b) for tangential flow microfiltration of minute virus of mice. Higher wall shear rates have also been reported (Akeprathumchai et al, 2004). Since human influenza virus is known to be fragile and easily destroyed, the actual wall shear rate used in a manufacturing process should be sufficiently low to maximize isolation of intact virus particles and minimize damage to virus particles by shear forces during cross flow.…”
Section: Discussionmentioning
confidence: 97%
“…While results are cell culture and pH-dependent, reductions in DNA concentrations of 1-3 log 10 reduction value (LRV) and HCP levels of 0.2-0.8 LRV have been reported [16,20]. Viruses have also been shown to precipitate at acidic pH conditions, resulting in 3-4 LRV murine leukemia virus removal [22,23]. For pH-sensitive molecules, product recovery as low as 40% has been reported, though recovery of greater than 90% is typical [11,20].…”
Section: Key Termsmentioning
confidence: 96%
“…Notably, positively charged flocculants, in particular polyamines (Peram et al, ), divalent cations (Romero et al, ; Shpritzer et al, ), chitosan (Riske et al, ), and polydiallyldimethylammonium chloride (PDADMAC) (McNerney et al, ; Zhao et al, ) have been shown to be successful in inducing flocculation as a result of interactions between the flocculant and the negatively charged surfaces of cells and cell debris. A key benefit of flocculation is a potential reduction in process related impurities such as HCP, host DNA, and viruses (Akeprathumchai et al, ). However, purification performance in this step is culture dependent (Roush and Lu, ) and it would be challenging to develop this step as an alternative to downstream polishing chromatography steps.…”
Section: Introductionmentioning
confidence: 99%